2016
DOI: 10.1039/c6ob00396f
|View full text |Cite
|
Sign up to set email alerts
|

The effect of photoisomerization on the enzymatic hydrolysis of polymeric micelles bearing photo-responsive azobenzene groups at their cores

Abstract: The design of stable polymeric micelles that can respond to specific stimuli is crucial for the development of smart micellar nanocarriers that can release their active cargo selectively at the target site, thus diminishing the therapeutic limitations due to non-selective damage to healthy tissues. Here we report the design and synthesis of photo- and enzyme-responsive amphiphilic PEG-dendron hybrids bearing one, two or four enzymatically cleavable azobenzene end-groups. These dual-responsive hybrids can respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…mPEG 5 kDa -allyl and mPEG 5 kDa -NH 2 were prepared as was described in a previously reported procedure …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…mPEG 5 kDa -allyl and mPEG 5 kDa -NH 2 were prepared as was described in a previously reported procedure …”
Section: Methodsmentioning
confidence: 99%
“…mPEG 5 kDa -allyl and mPEG 5 kDa -NH 2 were prepared as was described in a previously reported procedure. 29 mPEG 5 kDa -Propargyl. Methoxy poly(ethylene glycol) (M n = 5 kDa, 5.00 g, 1 mmol), KOH (1.68 g, 30 mmol, 30 equiv), and 80% propargyl bromide in toluene (3.25 mL, 30 mmol, 30 equiv) were reacted in toluene (50 mL) following a previously reported procedure.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Because of good antifouling property, low toxicity, and biocompatibility, poly(ethylene glycol) (PEG) is often used as a hydrophilic material, is modified to the surface of nanocarriers to increase their stability, resist protein adsorption in vivo, and prolong the circulation of nanocarriers in the body [30,31]. Consequently, most of enzyme-responsive LDBCs used PEG as a hydrophilic linear link to hydrophobic branches which can be hydrolyzed by lipase or amidase [32,33,34]. However, a large number of studies and clinical results have shown that PEG materials are slowly showing many shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] By selectively incorporating certain functional groups, such responsive materials can undergo a number of property changes as a result of external influences, including non-chemical stimuli such as light 6 or temperature, [7][8][9] or through chemical stimuli such as changes in pH, 6,8,10 redox reactions, [11][12][13][14] or dynamic-covalent, 15 and supramolecular interactions. 2,[16][17][18] Photoresponsive materials often demonstrate reversible isomerization upon irradiation and commonly include materials with azobenzene moieties 19,20 or spiropyrans. 21 Polymers with pH-responsive characteristics most often contain weak acid or base functional groups that lead to ionization or neutralization when exposed to a change in pH.…”
mentioning
confidence: 99%